Investigation of Lade-Kim Plastic Potential Applicability under Various Stress Paths for Rockfill Materials - Liping Chen; Shihai Bian; Xiaokai Niu; Yongbo Zhao (Advances in Materials Science and Engineering)
The dilatancy behavior of rockfill materials shows obvious stress path dependence. Lade-Kim plastic potential equation has been proposed for a long time to model the mechanical behavior of sand and concrete materials. However, it lacks the verification of rockfill materials, especially under various stress paths. In this paper, the dilatancy performance of coarse-grained materials under various stress paths is investigated, and then the dilatancy equation description and verification method based on Lade-Kim plastic potential are given. The applicability of Lade-Kim plastic potential for different stress path tests, such as conventional triaxial tests, constant P tests, and constant stress (increment) ratio tests, are verified and evaluated. It is found that Lade-Kim plastic potential is difficult to consider the influence of stress path. Finally, the Lade-Kim plastic potential, together with nonlinear dilatancy equation, is evaluated by changing the dilatancy equation in the framework of generalized plasticity. Lade-Kim plastic potential is suitable for constant stress increment ratio loading experiments and special care should be taken when applied to other stress paths. These works are helpful to understand stress path dependence of dilatancy behavior for rockfill materials and is beneficial for the establishment of stress path constitutive model.